The relation between C-reactive protein (C-RP) and coronary artery lesion in patients with unstable angina pectoris - Akbulut, M; Ilkay, E; Karaca, I; Özbay, Y; Kiliçoglu, E; Arslan, N (Medimond S R L, 2000)
[Abstract Not Available]
3rd International Congress on Coronary Artery Disease -- OCT 02-05, 2000 -- LYON, FRANCE
Keywords: Myocardial-Infarction; Disease